More than our pain : affect and emotion in the era of Black Lives Matter - Hinderliter, Beth, 1973-; Peraza, Steve (SUNY series in African American studies., 2021)
"Covering rage and grief, as well as joy and fatigue, examines how Black Lives Matter activists, and the artists inspired by them, have mobilized for social justice"--